1991
DOI: 10.1136/gut.32.6.645
|View full text |Cite
|
Sign up to set email alerts
|

Prostaglandin protects against bile salt induced increases in proton permeation of duodenal brush border membrane.

Abstract: A direct protective action of prostaglandin on luminal cell membranes was investigated by preincubating rabbit duodenal brush border membrane vesicles with prostaglandin E, (PGE,) before incubation with bile salts. Membrane perturbation was assessed by measuring the net proton permeability (P.,).Bile salts (deoxycholate, glycodeoxycholate, and taurodeoxycholate; 041-1.0 mmol/l) resulted in concentration dependent increases in P.,: from (mean (SE)) 5.42 (0.17) (n=20) to 8.44 (0.24)x10-4 (n=13) cm/s with 0.5 mmo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

1992
1992
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 23 publications
(5 reference statements)
0
4
0
Order By: Relevance
“…16 17 In vitro studies have shown that PGE2 exerts a direct protective action on duodenal luminal cell membrane vesicles incubated with deoxycholate. '7 These findings suggest that the mucosal eicosanoid response to intraluminal irritants is a protective response.…”
Section: Discussionmentioning
confidence: 99%
“…16 17 In vitro studies have shown that PGE2 exerts a direct protective action on duodenal luminal cell membrane vesicles incubated with deoxycholate. '7 These findings suggest that the mucosal eicosanoid response to intraluminal irritants is a protective response.…”
Section: Discussionmentioning
confidence: 99%
“…In Necturus antrum, taurocholate increased apical membrane conductance associated with an intracellular acidification (Kiviluoto et al 1989). Similarly, in isolated rabbit duodenal brush-border membrane vesicles bile salts increased proton permeability, and this increase was ameliorated by PGE2 (Zhao & Hirst, 1991). Thus, one mechanism for the protective action of prostaglandins is the reduction in apical membrane proton permeability, through pathways yet to be defined.…”
Section: Discussionmentioning
confidence: 96%
“…Bile acids, being amphiphilic compounds, are also able to directly interact with the lipid component of membranes. Interacting with membranes, bile acids can significantly change their structure and functions (detergent action) [ 14 , 15 , 16 , 17 ], as well as induce transmembrane transport of protons (protonophore action) [ 18 , 19 ] and divalent ions (ionophore action) [ 20 , 21 , 22 ]. At the same time, further studies are needed to elucidate the mechanisms of the protonophore and ionophore effects of bile acids in the mitochondria of animals and humans.…”
Section: Discussionmentioning
confidence: 99%
“…It is of note that hydrophobic bile acids are most effective in this case [ 14 , 15 , 16 , 17 ]. The protonophore [ 18 , 19 ] and ionophore [ 20 , 21 , 22 ] effects of bile acids are also known (see the next section for more details).…”
Section: Introductionmentioning
confidence: 99%